Integration of Smartwatches in Low-Cost Virtual Environments: A Systematic Literature Review with Emphasis on Cardboard Devices - de Castro, Murilo Santos; Gomes, Pedro Raphael Inácio; Nascimento, Thamer Horbylon (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
In this work, we investigated the integration between smartwatches and Cardboard devices for interaction in low-cost virtual environments. We analyzed five related works that explored this integration and discussed the main trends and challenges identified. The results revealed that different interaction methods, such as on-screen gestures, physical movements, and physiological sensors, were employed in the works. The integration between smartwatches and Cardboard devices presents a promising field for future research. New interaction methods, improvements in gesture recognition algorithms, and the expansion of additional device options are some of the identified research opportunities. This integration can offer a more immersive and interactive experience in virtual reality, making it more accessible and engaging for users. Future work can focus on refining these approaches, considering different devices, and exploring aspects related to usability and user acceptance. This work contributed to understanding the evolution and possibilities of integrating smartwatches and Cardboard devices, paving the way for innovations in this promising field of low-cost virtual reality.